FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN DI PT MAGELANG PUTRA JAYA MOTOR - Budihermanto, Iwan (JAB (Jurnal Akuntansi & Bisnis), 2017)
Along with the changing times and growing competition motorcycle industry in Indonesia, so the auto companies, especially in the field of motorcycleshould be able to determine the appropriate marketing strategy for their business can survive and win the competition. Many factors into consideration before purchasing a product consumers. The purpose of this study was to determine the effect of product quality, price, promotion and after-sales service to the buying decision. This study is a descriptive type of research, ie research that describes the objects that relate to decisions of a general nature. The population in this study were all consuments at the PT Magelang Putra Jaya bought aÂ Suzuki motorcycle. The sample in this study were 55consuments at the PT Magelang Putra Jaya Motor who bought a Suzuki motorcycle was taken by accidental sampling. The results prove that the three independent variables namely product quality, price, and after-sales service has a positive and significant effect on the dependent variable, namely SuzukiÂ motorcycle purchase decision. While the promotion of the independent variable has no significant effect for the respondent in determining the decision to buy a Suzuki motorcycle. The results of multiple regression test showed That all independent variables (product quality, price, promotion, and after-sales service) a positive influence on purchase decisions. The greatest positive influence on purchase decisions Suzuki motorcycle on PT Magelang Putra Jaya Motor are on a variable price with a coefficient of 0.347, followed by variable sales servis with a coefficient of 0.257, then the variable quality of the product with a coefficient of 0.146, while the most influential variables are low and do not signify that promotion of the value of the variable coefficient of 0.077.Key words: decision of purchase, product quality, price, promotion, sales service.